Analysis of Content and Relationship Dimensions of KH Ahmad Dahlan's Interpersonal Communication in Facing Conflict - Rilo Pambudi; Anang Sujoko; Reza Safitri (Sahafa Journal of Islamic Communication, 2024)
This study discusses the analysis of KH Ahmad Dahlan's interpersonal communication and small group communication in dealing with conflict, especially as depicted in the film "Sang Pencerah." KH Ahmad Dahlan is an important figure in the history of the development of Islam in Indonesia, particularly through the founding of the Muhammadiyah organization. This study aims to reveal KH Ahmad Dahlan's interpersonal and small group communication skills in addressing conflicts. The method used in this research is descriptive-interpretative with a qualitative approach. Data collection techniques include Ethnographic Content Analysis (ECA) of the film "Sang Pencerah" and in-depth interviews with relevant informants. The results of the research show that KH Ahmad Dahlan has excellent interpersonal and small group communication skills, which are reflected in the scenes in the film "Sang Pencerah" and reinforced by interviews with sources. These communication skills, especially in terms of openness and closeness, play a crucial role in his efforts to address and resolve conflicts that arise during his preaching process. These findings can serve as a reference for future research in understanding the role of interpersonal and small group communication in dealing with conflict and highlight the importance of an effective communicative approach in spreading reform ideas and facing resistance from conservative groups Keywords:, Content analyis, Interpersonal Communication, KH Ahmad Dahlan